Social Challenges to the Education of Orphaned and Vulnerable Children in Eleme, Nigeria - I. Eneji, Rosemary; Archibong , Esther Patrick (Richtmann Publishing, 2021)
Nigerian children under prolonged suffering because of loss of parents are faced with several challenges such as dropping out of school; in some cases, they may even be taken out of school to care for the home.Â In this study, we determined the challenges (financial, emotional and psychological) to the education of orphaned and vulnerable children in Eleme Local Government Area of Rivers State, Nigeria. All the 396 orphans in orphanages in the study Area constituted the study population. A Questionnaire captioned â€œthe challenges to the education of orphans and vulnerable children, a case study of Eleme Local Government Areas of Rivers Stateâ€, was developed for the study. Whether male or female, the children held that financial situations and emotional stress, to a high extent affected their education. The children attempt to cope with these challenges by being frugal, seeking company among themselves, and trying to develop the ability to manage their emotions. Clearly, the provision of access to finance (e.g., through special bursaries and grants) and guidance and counselling professionals will enhance the continuity and performance of orphans and vulnerable children in the schools. Â Received: 4 March 2021 / Accepted: 24 May 2021 / Published: 8 July 2021